2000
DOI: 10.1016/s1201-9712(00)90104-8
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous spleen rupture during typhoid fever

Abstract: Typhoid fever currently is an uncommon disease in western countries, and cases usually are imported from endemic areas.1 The most common complications are intestinal bleeding or perforation and necrotizing cholecystitis, although hepatitis, myocarditis, nephritis, and meningitis may occur. Spontaneous spleen rupture during typhoid fever is a known but rare complication. This report describes a new case and reviews the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…In Kenya, Berkley et al (1999) reported overall incidence of bacteraemia (7.8 %) in children with severe malaria and 12.0 % in children fewer than 30 months of age. There has been a reported case of concurrent falciparum malaria and Salmonella bacteraemia in travelers from developing countries (Gopinath et al, 1995;Jensenius et al, 1998;Julia et al, 2000). In Nigeria,…”
mentioning
confidence: 99%
“…In Kenya, Berkley et al (1999) reported overall incidence of bacteraemia (7.8 %) in children with severe malaria and 12.0 % in children fewer than 30 months of age. There has been a reported case of concurrent falciparum malaria and Salmonella bacteraemia in travelers from developing countries (Gopinath et al, 1995;Jensenius et al, 1998;Julia et al, 2000). In Nigeria,…”
mentioning
confidence: 99%
“…This is a known complication 1 but spontaneous splenic injury due to typhoid fever has also been reported. 4 Our case demonstrates the potential difficulty in diagnosing typhoid fever, in part because of the relatively low sensitivity of blood, urine and stool cultures. The negative results of the bone marrow culture likely reflects the 14-day course of antibiotics.…”
Section: Drug-resistant Strainsmentioning
confidence: 87%
“…Rupture usually occurs during the first week although delayed rupture cases are well documented [35]. Stephenson and DuBois showed in a recent report that patients requiring less than 4 U or 40 mL/kg of PRBC for resuscitation can be managed conservatively [36].…”
Section: Discussionmentioning
confidence: 99%